Theoretical Approaches to Political Stability: How Do Theories Interpret the Factors Influencing It? - Armen Mirzoyan (Journal of Political Science: Bulletin of Yerevan University)
Political stability is a crucial concept within political science, yet its theoretical foundations and influencing factors are often dispersed across various perspectives. This article presents the first comprehensive attempt to synthesize and analyze the theoretical approaches to political stability within a single work. Drawing from both political science and sociology, this study aims to explore how political stability shapes and is shaped by political, economic, social, and cultural systems. By examining the reciprocal relationships between these systems and political stability, the article identifies key theoretical frameworks that explain its trends and impacts. Notably, this is the first effort to address these theories in a unified manner, filling a gap in both Armenian political science literature and broader global scholarship. This work contributes to a deeper understanding of the factors that influence political stability and offers insights into their implications for societal development.